2010
DOI: 10.1074/jbc.m109.080572
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation/Phosphorylation Cycling at Ser10 Controls Both Transcriptional Activity and Stability of Δ-Lactoferrin

Abstract: ⌬-Lactoferrin (⌬Lf) is a transcription factor that up-regulates DcpS, Skp1, and Bax genes, provoking cell cycle arrest and apoptosis. It is post-translationally modified either by O-GlcNAc or phosphate, but the effects of the O-GlcNAc/phosphorylation interplay on ⌬Lf function are not yet understood. Here, using a series of glycosylation mutants, we showed that Ser 10 is O-GlcNAcylated and that this modification is associated with increased ⌬Lf stability, achieved by blocking ubiquitin-dependent proteolysis, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 66 publications
2
45
0
Order By: Relevance
“…Answering such questions will depend on time-resolved mapping of O-GlcNAcylation sites on both coand post-translationally O-GlcNAcylated proteins. On a more functional level, O-GlcNAc is a cellular stress response 6,35 that is also nutrient responsive [39][40][41] , and so it seems likely that cotranslational O-GlcNAcylation is an adaptive response enabling protection of nascent chains during times of stress or high metabolic flux, a view that is consistent with the protective effects of increased O-GlcNAc in various models 42 and the effects of altered O-GlcNAc levels on the levels of some proteins [7][8][9]37 .…”
Section: Discussionmentioning
confidence: 61%
“…Answering such questions will depend on time-resolved mapping of O-GlcNAcylation sites on both coand post-translationally O-GlcNAcylated proteins. On a more functional level, O-GlcNAc is a cellular stress response 6,35 that is also nutrient responsive [39][40][41] , and so it seems likely that cotranslational O-GlcNAcylation is an adaptive response enabling protection of nascent chains during times of stress or high metabolic flux, a view that is consistent with the protective effects of increased O-GlcNAc in various models 42 and the effects of altered O-GlcNAc levels on the levels of some proteins [7][8][9]37 .…”
Section: Discussionmentioning
confidence: 61%
“…O-GlcNAcylation stabilizes ⌬-lactoferrin and retains a basal level of transcriptional activity. Upon activation, ⌬-lactoferrin is phosphorylated at S10, which promotes transcription and subsequent degradation through K379 polyubiquitination (27). These studies point to the idea that protein functions can be precisely controlled by dynamic and coordinated changes in O-GlcNAcylation, phosphorylation, and ubiquitination.…”
Section: O-glcnac Modification and Its Interplay Withmentioning
confidence: 89%
“…⌬-lactoferrin expression is down-regulated in cancer cells, whereas its highlevel expression is correlated with a good prognosis in human breast cancer (25). It has been shown that ⌬-lactoferrin is reciprocally O-GlcNAcylated and phosphorylated at S10 (26,27). O-GlcNAcylation stabilizes ⌬-lactoferrin and retains a basal level of transcriptional activity.…”
Section: O-glcnac Modification and Its Interplay Withmentioning
confidence: 99%
“…Excessive O-GlcNAcylation has been shown to block proteasome activity and proteasomedependent degradation of Sp1, p53, and delta-lactoferrin (49)(50)(51)(52). Moreover, knocking down OGT activity leads to proteasome activation (51).…”
Section: Discussionmentioning
confidence: 99%